Time perception in carceral liminality: From a blocked present to future orientation in young prisoners - Maiorano, Antonietta; De Luca Picione, Raffaele (Form@re - Open Journal per la formazione in rete, 2025)
This study analyses the perception of time among young prisoners, focusing on the liminal condition experienced within prison. Using a qualitative approach, interviews were conducted to explore how imprisonment influences the perception of time, highlighting the sense of wasted, suspended time and the centrality of educational activities as tools for accelerating and activation the temporal dimension. The results show that the absence of activities and overcrowding aggravate the perception of immobility and empty time, negatively affecting the psychological well-being of prisoners. The possibility of participating in educational projects, on the other hand, is perceived as an opportunity to set time in motion again, to project oneself into future plans, transforming the liminal experience from suspension into a transformative experiential space. The implications concern prison policies aimed at enhancing educational opportunities and promoting social reintegration through educational programmes and partnerships with external stakeholders. Percezione del tempo nella liminalità carceraria: dal presente bloccato al movimento verso il futuro in giovani detenuti. Questo studio analizza la percezione del tempo tra i giovani detenuti, focalizzandosi sulla condizione di liminalità vissuta all’interno del carcere. Utilizzando un approccio qualitativo, sono state condotte interviste per esplorare come la detenzione influenzi la percezione temporale, evidenziando il senso di tempo sprecato, sospeso e la centralità delle attività educative quali strumenti di accelerazione e dinamizzazione della dimensione temporale. I risultati mostrano che l’assenza di attività e il sovraffollamento aggravano la percezione di immobilità e di tempo vuoto, influenzando negativamente il benessere psicologico dei detenuti. La possibilità di aderire a progetti educativi, invece, è avvertita come opportunità di rimettere in movimento il tempo, di riproiettarsi in una progettualità futura, trasformando l’esperienza liminale da sospensione in direzione di spazio esperienziale trasformativo. Le implicazioni riguardano politiche penitenziarie orientate a potenziare l’offerta formativa e a favorire il reinserimento sociale attraverso programmi educativi e collaborazioni con il mondo esterno.